2020
DOI: 10.1590/1414-431x20209299
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA LINC01268 promotes cell growth and inhibits cell apoptosis by modulating miR-217/SOS1 axis in acute myeloid leukemia

Abstract: The aim of this study was to evaluate the pathogenic role of newly identified long non-coding (lnc)-RNA LINCO1268 in acute myeloid leukemia (AML), and investigate its therapeutic potential. The expression level of LINC01268 in AML was measured by quantitative PCR (qPCR). The viability, cell cycle progression, and apoptosis of AML cells were measured by CCK-8 assay and flow cytometry, respectively. The interaction between LINC01268 and miR-217 were predicted by the miRDB website, and then verified by luciferase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…LINC01268 is an independent prognostic immune-related marker that can reduce the proliferation and metastasis of cancer cells in neuroblastoma [35]. Increased plasma levels of LINC01268 are associated with poor prognostic factors in myelo brosis [36], and LINC01268 positively regulates SOS1 expression by sponging miR-217 to promote acute myeloid leukemia cell viability and cell cycle progression but inhibit apoptosis [37]. We also identi ed that LINC01268, as an oncogene, can promote epithelial-mesenchymal transition (EMT) in PaCa through the miR-217-KIF2A-PI3K/AKT axis [24].…”
Section: Discussionmentioning
confidence: 99%
“…LINC01268 is an independent prognostic immune-related marker that can reduce the proliferation and metastasis of cancer cells in neuroblastoma [35]. Increased plasma levels of LINC01268 are associated with poor prognostic factors in myelo brosis [36], and LINC01268 positively regulates SOS1 expression by sponging miR-217 to promote acute myeloid leukemia cell viability and cell cycle progression but inhibit apoptosis [37]. We also identi ed that LINC01268, as an oncogene, can promote epithelial-mesenchymal transition (EMT) in PaCa through the miR-217-KIF2A-PI3K/AKT axis [24].…”
Section: Discussionmentioning
confidence: 99%
“…LINC01268 has been recently described as being upregulated in AML samples [ 52 , 53 ]. In a first work LINC01268 has been described as acting as competing endogenous RNA (ceRNA) via sponging the onco-suppressor miR-217 which in turns inhibits at the post-transcriptional level SOS1 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…In a first work LINC01268 has been described as acting as competing endogenous RNA (ceRNA) via sponging the onco-suppressor miR-217 which in turns inhibits at the post-transcriptional level SOS1 mRNA. By modulating miR-217/SOS1 regulatory axis, LINC01268 promotes cell growth and inhibits apoptosis [ 52 ]. The downregulation of miR-217 in AML cells was described also by Xiao et al, being proposed acting as a tumor suppressor by directly targeting KRAS [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al. 32 found that the proportion of SOS1 inhibition cells staying in G1 phase increased compared with the NC group in SOS1 inhibition, because activation of the PI3K-AKT signaling pathway promotes malignant cell proliferation induced by BCR-ABL. Our findings provide a rationale for therapeutic targeting of SOS1 levels to inhibit the proliferation of CML cells.…”
Section: Discussionmentioning
confidence: 99%